Cellular effects mediated by pathogenic LRRK2: homing in on Rab-mediated processes. (15th February 2017) - Madero-Pérez, Jesús; Fdez, Elena; Fernández, Belén; Lara Ordóñez, Antonio Jesús; Blanca Ramírez, Marian; Romo Lozano, María; Rivero-Ríos, Pilar; Hilfiker, Sabine
Abstract : Leucine-rich repeat kinase 2 (LRRK2) is a key player in the pathogenesis of Parkinson's disease. Mutations in LRRK2 are associated with increased kinase activity that correlates with cytotoxicity, indicating that kinase inhibitors may comprise promising disease-modifying compounds. However, before embarking on such strategies, detailed knowledge of the cellular deficits mediated by pathogenic LRRK2 in the context of defined and pathologically relevant kinase substrates is essential. LRRK2 has been consistently shown to impair various intracellular vesicular trafficking events, and recent studies have shown that LRRK2 can phosphorylate a subset of proteins that are intricately implicated in those processes. In light of these findings, we here review the link between cellular deficits in intracellular trafficking pathways and the LRRK2-mediated phosphorylation of those newly identified substrates.